IMPLEMENTASI KURIKULUM 2013 BERBASIS PENDEKATAN SAINTIFIK DALAM PENGAJARAN BAHASA INGGRIS SMA/SMK BERBASIS TEKS - Ambalegin Ambalegin; Suhardianto Suhardianto (ASOSIASI IDEBAHASA KEPRI, 2020)
The implementation of the Curriculum 2013 is noble because it implements attitudes, knowledge, and skills integrated in every subject. The curriculum 2013 uses a scientific approach in each teaching implementation thus the students are taught to prioritize inductive compared to deductive reasoning. English is a core lesson and a skill in SMA/SMK must be taught by teachers who have competence in transferring knowledge, but they are constrained in the application of a scientific approach to text-based English teaching (texbook-based approach). The purpose of this training is to open the horizons of English teachers in applying two approaches in teaching English at SMA/SMK level in the classroom. The method implemented was public education and training with the techniques of lecturing, discussing, and demonstrating. The result of this training was the improvement of the teachers’ capability in teaching English by collaborating the scientific approach and textbook-based approach in the classroom. This training was the importance of developing the potential of students to become human beings who believe and fear God Almighty, have good morality, health, knowledge, capability, creativity, and independence, and be democratic and responsible citizens.